Analysis of the tourism infrastructure of the cities of Central Kazakhstan - Mamrayeva, D.G.; Tashenova, L.V. (BUKETOV BUSINESS REVIEW, 2021)
Object: the research of the current state of the tourist infrastructure of the cities of Central Kazakhstan, in particular, the analysis of urban transport infrastructure, as well as the main indicators of the activities of accommodation facilities during the quarantine period due to the COVID-19 pandemic. Methods: for achieving the goal of the research, general scientific methods were widely used, in particular the method of content analysis, which made it possible to organize and structure the main scientific research related to the study of urban tourist infrastructure; method of analysis, which made it possible to assess the state of urban transport infrastructure and accommodation facilities in the region; a generalization method aimed at establishing existing relationships between the considered economic objects and phenomena; the method of graphic interpretation, which made it possible to visualize the results obtained. Results: the analysis of the state tourist infrastructure in the cities of the Karaganda region was carried out, special emphasis was made on the research of urban transport infrastructure, the dynamics of passenger traffic by mode of transport in conditions of quarantine restrictions were given, the availability of urban transport was reflected in terms of the possibility of renting cars for tourists. In connection with the increased demand for domestic tourism, the main motives of travel, geographic directions and the structure of expenses of domestic tourists have been studied. The main indicators of accommodation facilities (volume of services, occupancy, average cost, etc.) were also analyzed, the dynamics of the number of visitors served by categories and types of accommodation facilities was reflected, the impact of the pandemic on some aspects of the activities of accommodation companies was shown. Conclusions: the results obtained made it possible to give a comprehensive assessment of the state of the tourist infrastructure, namely, the transport and accommodation infrastructure in the cities of the Karaganda region, to identify the level of availability of tourist services in terms of car rental, the availability of category hotels and the level of their service.